Mental health and the built environment more than bricks and mortar? - Halpern David (London Taylor & Francis, 1995)
This text explores the relationship between the planned or built environment and the occurrence of mental ill-health. It discusses topics such as the impact of the environment as a source of stress and the effects that the environment can have on the qual
Keywords: Environment; Environmental psychology; Mental health; Mental illness